2011
DOI: 10.1177/1545968311407517
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Threshold of Rehabilitation Involving Brain-Derived Neurotrophic Factor Is Required for Poststroke Recovery

Abstract: Data suggest that there is a critical threshold of rehabilitation, below which recovery will not occur, and that BDNF mediates functional recovery. The use of intensive rehabilitation therapies for stroke patients is strongly supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 49 publications
4
122
2
Order By: Relevance
“…31 Recent studies in rodents have shown that this recovery is most likely because of acivitydriven changes in BDNF. 19 In the present study, we failed to see any significant elevation in BDNF levels after stroke, indicating that the endogenous neuroplastic mechanisms involved in improving motor functions in young, are lacking or impaired in aged mice. Further, treatment with CX1837 resulted in a smaller increase in BDNF levels compared with previous published data in young mice (75% increase in young versus 54% increase in aged mice).…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…31 Recent studies in rodents have shown that this recovery is most likely because of acivitydriven changes in BDNF. 19 In the present study, we failed to see any significant elevation in BDNF levels after stroke, indicating that the endogenous neuroplastic mechanisms involved in improving motor functions in young, are lacking or impaired in aged mice. Further, treatment with CX1837 resulted in a smaller increase in BDNF levels compared with previous published data in young mice (75% increase in young versus 54% increase in aged mice).…”
Section: Discussioncontrasting
confidence: 66%
“…This dynamic relationship between BDNF and recovery has been previously identified by other authors to be critical, 8 with BDNF levels not only need to be increased, but also need to reach a critical threshold in order for recovery to be evident. 19 As the more modest levels of recovery observed in aged animals could have been attributed to age-related deficits in BDNF production, we next investigated whether localized delivery of BDNF could enhance the effects of CX1837. Our results here indicated that local hydrogel delivery of BDNF alone was able to enhance functional recovery in aged mice (36% gain of function at 6 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 For example, blocking brain-derived neurotrophic growth factor inhibits recovery after ischemia, 13,14 whereas effective rehabilitation induces an enhancement of brain-derived neurotrophic growth factor. 15 Rehabilitation likely induces usedependent activation of intact tissue bordering the stroke that mediates neuroplastic changes and subsequent functional improvement. This possibility, although suggested previously, 8,16,17 has not been directly tested in the earliest stages of poststroke rehabilitation.…”
Section: Introductionmentioning
confidence: 99%